Aspidistra xichouensis (Asparagaceae), a new species from the karst region in southeastern Yunnan, China - Cai, Lei; Pan, Bo; Lin, Chun-Rui; Dao, Zhi-Ling; Hu, Guang-Wan (Phytotaxa, 2020)
Aspidistra xichouensis, a new species of Asparagaceae from Xichou County, Yunnan Province, China, is described and illustrated. The new species is similar to A. minutiflora, A. graminifolia and A. cylindrica in the shape of leaf blade and the size and structure of flowers, but can be easily distinguished mainly by the conspicuous petiole, upright peduncle, and erect flowers with 4(–5) perianth lobes. The results of comparisons with the related species are also provided.